Estimating consumption in the HFCS: Experimental results on the first wave of the HFCS - Pierre Lamarche (European Central Bank (ECB), 2017)
In this paper, we estimate consumption in the first wave of the Eurosystem Household Finance and Consumption Survey for a subset of countries that account for around 85% of the aggregate final consumption expenditure of households in the euro area. For this purpose we use the methodology described by Browning et al. (2003), taking advantage of the few questions on consumption asked to households participating in the survey and information on consumption collected in the Household Budget Surveys. Using also the framework developed for statistical matching, we give assessments of the uncertainty related to this kind of estimation. We find that the quality of estimation varies greatly across countries and in general is sensitive to the Conditional Independence Assumption implicitly made through this exercise. At any rate, estimations of consumption (provided throughout this paper) should be used with caution, bearing in mind that they rely on strong assumptions.
Keywords: D12; D14; D31; 330; consumption; income; wealth; survey; HFCS; HBS; statistical matching